DETECTION OF NON-ADHERENCE TO ANTI-HYPERTENSIVE TREATMENT THROUGH THE USE OF THE ELECTRONIC PRESCRIPTION SYSTEM IN PATIENTS REFERRED TO A TERTIARY HYPERTENSION CLINIC. (June 2018) - Baño, D.G. Mena; Atauje, A. Arias; Laguna, M. Gonzalez; Zamora, A. Padulles; Barrio, S. Fernandez; Valverde, L. Blanch; Melilli, E.
Abstract : Objective: To know and evaluate the level of adherence to antihypertensive treatment through the information provided by the electronic prescription computerized system. Figure. No caption available. Design and method: A retrospective, cross-sectional study was conducted in the tertiary hypertension clinic of the Bellvitge[Combining Acute Accent]s Hospital. Patients visited from June 2015 to July 2017 and with resistant hypertension diagnosis and/or aged less than 50 years were included. The data analyzed from the electronic prescription included: class of drug, prescribed dose and number of boxes collected in pharmacy each month. Adherence to the medication was evaluated during a 24-month long follow-up using the formulas: Number of theoretical boxes = (starting treatment date – final date of follow-up) × (daily intake unit)/(number of tablets of each box). Adherence (%) = number of boxes actually dispensed/number of theoretical boxes x100. The data analysis was performed using the SPSS package, a level of significance P < / = 0.05 was set in all cases. Results: We included 261 patients according to criteria. The average age was 61 ± 14.2 years, being 29.9% under 50 years. 84% of patients had resistance hypertension. (Table 1). Figure 1 shows the distribution by amount of drug classes. We detected an adherence to medication of less than 80% in 23.4% patients, between 80–95% in 28.1% and > 95% in 48.4% (Fig 2). Patients treated with < 2 classes of drugs had lower adherence (cut-off > 80%) compared to those taking > 3 classes (58.1% vs. 79.8% p < 0.001). Also, we observed an inverse correlation between age and adherence (r - 0.25 p 0.0001). Patients under 50 years had lower (average) adherence to those over (79.1 ± 32.2 % vs 96.2 ± 17.3 % p.0001). (Fig. 3) Conclusions: The low adherence rates detected with electronic prescription computerized system were similar to values published in previous studies based on more complex methods (use of questionnaires, urinary metabolites, electronic boxes). Despite its intrinsic limitations, our method allowed to detect an high percentage of non-adherence. In our cohort, younger patients and those who take fewer drugs presented the lowest levels of adherence.